Hubungan Social Support dengan Hardiness Pada Ibu yang Bekerja di Pasar Tradisional Kota Solok - Maretha, Vyona Deyan; Dwatra, Free Dirga (CV. Causalita Dynamic Solutions, 2025)
This study aims to determine the relationship between social support and hardiness in mothers working in traditional markets in Solok City. Quantitative methods are used in this study. The Social Support Scale and Hardiness Scale are used to collect data from 100 samples for this study. Purposive sampling is used in the sample selection process. With the help of IBM SPSS Statistics 25 for Windows, the product moment correlation test for data analysis. The results of this study show a Pearson Correlation of 0.566, which means that there is a positive and significant relationship between social support and hardiness in mothers working in traditional markets in Solok City. Based on this test, the results show that H1 is accepted, namely that there is a relationship between social support and hardiness in mothers working in traditional markets in Solok City.